Education and Ultilization of the Anting-Anting Plant (Acalypha indica L.) as a Herbal Gastroprotective for Gastritis Prevention in the Community - Suci Wulandari; Basyariah Lubis; Aminah S.; Sunariati Sunariati (JURNAL PENGMAS KESTRA (JPK), 2026)
Gastritis is one of the primary health problems in Indonesia, with a high prevalence largely triggered by the uncontrolled use of non-steroidal anti-inflammatory drugs (NSAIDs) such as aspirin. Aspirin is known to induce gastric ulcers through direct irritation and the inhibition of prostaglandin production. As a preventive alternative, the anting-anting plant (Acalypha indica L.) contains phytochemicals such as flavonoids, saponins, tannins, and alkaloids, which are proven effective as gastroprotective or gastric mucosal protective agents. This community service activity aims to educate residents regarding the risks of NSAID side effects and to promote the utilization of anting-anting leaf extract to prevent gastric damage. The activity was implemented using an educational-participatory approach involving 45 respondents in the Lubuk Pakam region, consisting of health cadres, the elderly, and housewives. Evaluation was conducted by measuring knowledge levels using pre-test and post-test questionnaires, as well as a participant satisfaction survey. The results of the activity showed a sharp and measurable increase in clinical pharmacology literacy. Prior to the education, 82.2% of respondents had a poor level of knowledge regarding the side effects of aspirin. However, after the interactive counseling, 68.9% of respondents achieved a good knowledge category. Additionally, 84.4% of respondents expressed high satisfaction with the overall benefits of this community service program. This education successfully bridges laboratory research findings into the practical realm, which is expected to encourage the implementation of safer self-medication and rational therapy within the community.